Underground space needs an interdisciplinary approach. (May 2016) - Besner, Jacques
Highlights: Planning is necessary for multiple professions and in each there are different types of plans. Urban planning is in constant mutation. New issues, problems, techniques and ideas emerge in the field of underground space. ACUUS is an independent international NGO with a strong focus on cities. Abstract: During a very long period of time, civil engineers have been the only ones to be designated as the experts for underground space, while the planners and architects were the ones of the development at the surface. This silo approach to work is now a thing for the past in most major cities, but solving this fragmentation of the disciplines does not happen overnight. It first took a few thinkers to promote and publish on the subject, such as Edouard Utudjian, founder of GECUS in 1937, and also that planners abandon their ambiguous position on this invisible space, become part of multi-disciplinary teams and participate in the dissemination of new knowledge, particularly through some international associations such as ACUUS. With biennial scientific conferences dating back to 1983, the organization actively promotes since partnerships amongst all actors in the field of planning, management, research and uses of urban underground space in all its forms. The originality of ACUUS comes from its success in attracting public, private and university levels into a cohesive network of mutual cooperation, which is not so common in international organizations.